2018
DOI: 10.1186/s12895-018-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Can an app supporting psoriasis patients improve adherence to topical treatment? A single-blind randomized controlled trial

Abstract: BackgroundTopical corticosteroid or corticosteroid/calcipotriol preparations are recommended first-line topical treatments of psoriasis, but a main cause for the lack of efficacy of topical treatments is considered low rates of adherence to topical drugs. Patient support by the use of applications (apps) for smartphones is suggested to improve medical adherence.Methods/designDesign: An investigator-initiated, single-center, single-blind, parallel-group, phase-4 clinical superiority randomized controlled trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Reminder programs using e‐mails, phone calls, text messages or smartphone applications can be helpful to counteract patients’ forgetfulness . The success rate of these programs in improving adherence is, however, inconsistent according to the literature, and depends on patients’ character and personality …”
Section: Strategies To Improve Treatment Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…Reminder programs using e‐mails, phone calls, text messages or smartphone applications can be helpful to counteract patients’ forgetfulness . The success rate of these programs in improving adherence is, however, inconsistent according to the literature, and depends on patients’ character and personality …”
Section: Strategies To Improve Treatment Adherencementioning
confidence: 99%
“…97 The success rate of these programs in improving adherence is, however, inconsistent according to the literature, and depends on patients' character and personality. 16,56,98,99 Simplifying treatment regimes and reducing pill burden are easy methods to enhance treatment adherence. Once-daily regimes with combined pharmacological agents are preferable, since they are more manageable for the patient.…”
Section: Strategies To Improve Treatment Adherencementioning
confidence: 99%
“…A 6‐month investigator‐initiated single‐site, parallel‐group, phase‐IV superiority block randomized controlled trial (RCT) with an allocation ratio of 1 : 1 was conducted according to the principles expressed in the Declaration of Helsinki as revised in 1983, the International Conference on Harmonisation Good Clinical Practice Guideline E6 (R2), and Danish national laws (clinicaltrials.gov registration NCT02858713). The protocol was approved by the Regional Ethics Committees on Health Research Ethics for Southern Denmark and the Danish Medicines Agency (EudraCT 2016‐002143‐42) . The study was conducted between 9 January 2017 and 29 August 2017 at an outpatient clinic for dermatology at Odense University Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was approved by the Regional Ethics Committees on Health Research Ethics for Southern Denmark and the Danish Medicines Agency (EudraCT 2016-002143-42). 22 The study was conducted between 9 January 2017 and 29 August 2017 at an outpatient clinic for dermatology at Odense University Hospital. Written informed consent was obtained from all patients at inclusion and prior to randomization.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a previous survey among people living with type 1 diabetes mellitus found that 40% of respondents reported being aware of self-management apps 12. Alongside the value of apps in patient self-empowerment, they can also facilitate patient communication with health professionals,13 improve treatment adherence,14 provide condition-specific education and enable remote condition monitoring 15 16…”
Section: Introductionmentioning
confidence: 99%